Pengaruh Aspek Manajemen Program Penanggulangan Tuberkulosis Paru, Pengetahuan Masyarakat, dan Aksesibilitas Masyarakat terhadap Capaian Penemuan Kasus Penderita Tuberkulois Paru - Ageng Prasetia; Kosasih Kosasih; Rulia Rulia (Jurnal Ners, 2025)
Pulmonary tuberculosis remains a major public health challenge in Indonesia, with suboptimal case detection rates. This study aims to analyze the influence of program management aspects, community knowledge, and community accessibility on the achievement of pulmonary tuberculosis case detection at community health centers (Puskesmas) in Sukabumi Regency. This research employed a quantitative approach using a census method, involving 58 respondents responsible for tuberculosis programs. Data were collected through interviews, questionnaires, and document analysis, and were subsequently analyzed using multiple linear regression. The findings indicate that all three independent variables program management aspects, community knowledge, and community accessibility have a positive and statistically significant influence, both simultaneously and partially, on the achievement of pulmonary tuberculosis case detection (p < 0.05). The coefficient of determination (R²) of 87.4% demonstrates that the combination of these variables explains a substantial portion of the variance in case detection achievement. These results suggest that improvements in program management, community education, and access to health services are critical to enhancing early detection of tuberculosis at the primary healthcare level.